Fatores que influem na sustentabilidade: um estudo dos municípios brasileiros - CASTRO, Mauro Lincon Meneses de (2024)
The perpetuation of life on planet Earth is intrinsically linked to environmental conditions. Therefore, faced with the accelerated consumption of natural resources, it is imperative to adopt precautionary measures. Aiming to contribute to the sustainable development of Brazilian cities and promote the well-being and improvement of the quality of life of its population, the Sustainable Cities Development Index (IDSC-BR) was created. This index aims to facilitate the implementation of the Sustainable Development Goals (SDGs) through data analysis. The IDSC-BR proposes to guide the sustainable development process of Brazilian municipalities, using indicators to identify the main needs of public managers and the specific challenges of each area. In this context, the present study aims to analyze the impact of IDSC-BR variables on the sustainability of Brazilian municipalities, thus contributing to a better understanding of sustainable development mediated by IDSC-BR, in the search for the designation of sustainable cities and the implications. characteristics in the competitiveness of these municipalities. The methodology used is characterized by being descriptive, quantitative and documentary research, which uses statistical indicators and criteria. To carry out this study, we selected 16 indicators were selected from a total set of 100 that form the database of the Sustainable Cities Development Index - Brazil (IDSC-BR) of 2022. In addition, 200 municipalities representing five delimited areas of Brazil for analysis. Data analysis was carried out using descriptive statistics, with the results summarized in a Microsoft Excel spreadsheet. With the support of PowerBI software, correlation analysis was carried out, aiming to identify, measure and graphically represent the associations between the selected variables and GDP per capita. The results indicate that there is almost non-existent correlation between the population's purchasing power and sustainability indicators. It was also observed that the municipalities in area 4 presented the worst performances in nine of the sixteen indicators analyzed, while the municipalities in area 2 demonstrated better results in six of the indicators. Among the indicators evaluated, energy vulnerability was the one that showed the highest correlation with GDP per capita. Limitations were found in relation to the database, which presented many incomplete data, as well as the lack of weighting for the importance of each indicator. It also highlights the need for future studies encompassing the use of data from primary sources, updated, complete and aligned to the same period.